2005
DOI: 10.1001/jama.293.15.1891
|View full text |Cite
|
Sign up to set email alerts
|

A Large High-Density Lipoprotein Enriched in Apolipoprotein C-I

Abstract: OW BIRTH WEIGHT IS ASSOCIated with cardiovascular risk factors and death in adulthood. 1 Differences in the size, molecular weight, composition, and quantity of lipoprotein subclasses are associated with coronary artery disease (CAD). 2 In our initial study of lipoprotein heterogeneity in cord blood, infants born small for gestational age (SGA) had higher levels of triglyceriderich very low-density lipoprotein (VLDL) and intermediate low-density lipoprotein (IDL) than infants born appropriate for gestational a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Additionally, there is a paucity of data available on fetal blood lipid concentrations. One study identified lipid profiles that differed in small-for-gestational-age infants compared to normal-weight infants, with increased levels of apo C-I–enriched high-density lipoproteins [ 14 ], however information is still lacking in this area. Maternal lipid concentrations have been correlated with fetal lipid concentrations at birth among women with diabetes, which highlights the importance of the maternal environment on the fetus during pregnancy [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, there is a paucity of data available on fetal blood lipid concentrations. One study identified lipid profiles that differed in small-for-gestational-age infants compared to normal-weight infants, with increased levels of apo C-I–enriched high-density lipoproteins [ 14 ], however information is still lacking in this area. Maternal lipid concentrations have been correlated with fetal lipid concentrations at birth among women with diabetes, which highlights the importance of the maternal environment on the fetus during pregnancy [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…In summary, cord samples SGA neonates presented atherogenic lipid profiles and impaired lipoprotein characteristics. 24,26,38 Other studies demonstrated the presence of large HDL-C subclasses enriched in apo-C-I in cord blood. These molecules appeared elevated in infants with lower birth weights and younger gestational ages and with significantly elevated total and large LDL cholesterol and LDL particle number, but lower total and VLDL triglycerides in contrast with SGA neonates.…”
Section: Lipid Profilementioning
confidence: 99%
“…These molecules appeared elevated in infants with lower birth weights and younger gestational ages and with significantly elevated total and large LDL cholesterol and LDL particle number, but lower total and VLDL triglycerides in contrast with SGA neonates. 38 Additionally, infants with a greater positive change in BMI z-score in the first 6 months presented a high proportion of saturated and low proportion of polyunsaturated plasma fatty acids (PUFA) at birth. Also, a tendency for a lower proportion of n-3 long-chain (LCPUFA) in infants with greater BMI z-score changes in the first 6 months was noticed.…”
Section: Lipid Profilementioning
confidence: 99%
“…The transfer of maternal cholesterol to the fetus through the umbilical cord might justify these effects. A previous study reported that low birth weight infants had lower HDL levels compared to their term counterparts [9,10]. There is still controversy over the association between maternal lipid profile and preterm delivery.…”
Section: Introductionmentioning
confidence: 99%